Erratum to: Recent developments in immobilizing titanium dioxide on supports for degradation of organic pollutants in wastewater-A review - Alhaji, Mohammed Haji; Khairuddin, Sanaullah; Afrasyab, Khan; Hamza, Abdulhamid M.; Muhammad, Ali M.; Mustapha, S. I.; Rigit, Andrew Ragai Henry; Bhawani, Showkat Ahmad (Springer Berlin Heidelberg, 2017)
The name of the author S.I. Mustapha contains errors in the original article. © 2017, Islamic Azad University (IAU).